2013
DOI: 10.3390/ijms141122906
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Functional Roles of the Polypyrimidine Tract-Binding Protein

Abstract: Polypyrimidine Tract Binding Protein (PTB) is an intensely studied RNA binding protein involved in several post-transcriptional regulatory events of gene expression. Initially described as a pre-mRNA splicing regulator, PTB is now widely accepted as a multifunctional protein shuttling between nucleus and cytoplasm. Accordingly, PTB can interact with selected RNA targets, structural elements and proteins. There is increasing evidence that PTB and its paralog PTBP2 play a major role as repressors of alternativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 178 publications
(192 reference statements)
2
100
0
Order By: Relevance
“…Our studies, however, revealed no P311 interaction or competition with either of them, indicating that the RRM region of eIF3b has multiple binding partners. RRM-containing genes represent about 0.5-1% of all human genes (67). Therefore, if the RRM represents the only P311 binding motif in the context of mRNA translation, the number of transcripts regulated by P311 should be relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies, however, revealed no P311 interaction or competition with either of them, indicating that the RRM region of eIF3b has multiple binding partners. RRM-containing genes represent about 0.5-1% of all human genes (67). Therefore, if the RRM represents the only P311 binding motif in the context of mRNA translation, the number of transcripts regulated by P311 should be relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…A modular protein architecture can also enable proteins to recognize non-contiguous sequences 23 and thus intervening RNA sequences can become important contributors to specificity 107109 . In addition, protein regions that link different RDBs can further modulate the contribution of each RBD to the protein’s overall RNA binding and specificity, and even promote cooperativity between RBDs 110 . Multiple RBDs with different inherent affinity distributions can also compensate for each other in a given protein and lead to uniform binding of an RBP to a wide range of diverse substrates (Fig.…”
Section: Specific Vs Non-specific Interactionsmentioning
confidence: 99%
“…EIF3GA is orthologous to human EIF3G, a component of the eIF3 complex involved in translation (Lasko 2000;Hinnebusch 2006). Many splicing regulators have been shown to also affect translation (e.g., Romanelli et al 2013;Maslon et al 2014); therefore, other examples of multifunctional RNA binding proteins exist. SHEP is an RNA binding protein that contains two RRM domains, is highly expressed in the nervous system of the fly (Brown et al 2014), and is involved in gravity sensing (Armstrong et al 2006).…”
Section: Identification Of Transcriptome-wide Regulatory Targets Of 5mentioning
confidence: 99%